Development of 153Sm-DTPA-SPION as a theranostic dual contrast agents in SPECT/MRI - Amir Gholami; Seyyed Hossein Mousavie Anijdan (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s): This study describes the preparation, biodistribution of 153Sm-DTPA-SPION after intravenous injection in rats. Materials and Methods: The chelator DTPA dianhydride was conjugated to SPION using a small modification of the well-known cyclic anhydride method. Conjugation was done at a 1: 4 (SPION: ccDTPA) molar ratio. Conjugation reaction was purified with magnetic assorting column (MACs) using high gradient magnetic field following incubation, the radio labeled conjugate was checked using RTLC method for labeling and purity checked. Results: The RTLC showed that labeling yield was above 99% after purification and the compound have good in vitro stabilities until 48 hr post injection in the presence of human serum. The biodistribution of 153Sm-DTPA-SPION in rats showed dramatic uptake in the reticuloendothelial system (RES) and their clearance is so fast in other organs especially in the blood. Biodistribution results show that after 30 min post injection more than 84% of injected activities were taken up by the liver and spleen (about 64% and 20%, respectively). Conclusion: Due to magnificent uptakes of this radiotracer in the liver and spleen and their fast clearance from other tissues, especially in blood, it is suggested that this radiotracer would be a potential candidate for RES theranostic purposes.